Analysis of Factors Causing Incomplete Filling of Medical Resumes at Pratama Clinic - Wijayanti, Rossalina; Delvia NB, Azza Ferista; Rachmawati, Ervina; Alfiansyah, Gamasiano (Indonesian Journal Publisher, 2024)
The number of incomplete inpatient medical resumes at the Pratama Clinic from January to March 2024 was 56.7%. This shows that there are still several items of medical resume forms that are not complete according to the SPM which is 100%. This research aims to analyze the factors causing incomplete filling out medical resume forms for inpatients at the Pratama Clinic. This type of research is qualitative with data collection techniques of in-depth interviews, observation, and documentation. The subjects in this study were 2 doctors, 4 nurses, and 2 medical records officer. Results research on factors causing incompleteness include lack of knowledge of doctors and nurses regarding filling time standards medical resume form, lack of responsibility of doctors and nurses towards filling, doctors and nurses have never attended filling training medical resume form, absence of SOP and strict punishment for doctors and nurses.